Design of Multisensor Automatic Fan Control System Using Sugeno Fuzzy Method - Robson, Willy; Ernawati, Iin; Nugrahaeni, Catur (Universitas Muhammadiyah Yogyakarta, 2021)
In the Decree of the Minister of Health number 1405, it is stated that a good temperature and humidity for the room is in the range 18 Â° C-28 Â° C and 40% -60% and if the temperature or humidity is above the stated range, a tool is needed to cool the room, one of which is is a fan and a device to humidify the room [1]. Then there are also problems regarding frequently forgetting to turn off fans that are no longer used. With this problem, it is necessary to have a system that can control the air conditioner, a system that can make the fan work automatically, that is, it can turn on and off and adjust the motor speed according to room temperature requirements when the fan is on. PIR (Passive Infrared) sensors and DHT-22 sensors are sensors that will be applied to this system as well as the application of the Fuzzy Sugeno Logic method to regulate the work of the system so that it can work automatically.